Sociodemographic Factors and Adolescent Attitudes Towards Family Planning Programs Related to Adolescent Marriage in Bali Province - Luh Seri Ani; Luh Nyoman Sumiati; Ni Kadek Ayu Dwi Utami Ds (Universitas Negeri Semarang in collaboration with Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI Tingkat Pusat) and Jejaring Nasional Pendidikan Kesehatan (JNPK), 2025)
Adolescent marriages in Bali Province are reported to be increasing. Sociodemographic factors and adolescents’ attitudes toward family planning programs are suspected to be related to adolescent marriage. Therefore, this study aims to analyze the relationship between demographic factors of adolescents’ attitudes toward family planning programs and the ideal age of marriage for adolescents. This study uses secondary data from the Program Performance and Accountability Survey of the National Population and Family Planning Agency of Bali Province in 2019. Cross-sectional studies were conducted among adolescents aged 10-24 years. The probability of selecting 668 adolescents for this study was determined using the proportional-to-size method. An adolescent’s marriage is determined based on the adolescent’s perceptions of the age of marriage before 21 years. Logistic regression tests were conducted to determine the relationship between access to information and the perception of marriage among adolescents. It was found that 87.9% of the adolescents perceive the age of marriage for women as≥ 21 years. Based on the results of the multivariate analysis, gender, rural residence, and access to information on family planning programs, adolescents’ attitudes toward FPPs and attitudes toward marriage before 21 years of age were associated with adolescents’ marriage. Factor demographic factors and adolescent attitudes increased the perception of the ideal age for marriage among adolescents. This finding suggests that demographic factors should be considered to increase the ideal age for adolescent marriage to further prevent the incidence of health and social problems resulting from child marriages.